Aortic Rupture During a Staged Endovascular Repair of a Thoracoabdominal Aneurysm. (2015) - Delloye, M.; Maurel, B.; Spear, R.; Hertault, A.; Azzaoui, R.; Tyrrell, M.; Sobocinski, J.; Haulon, S.
Abstract : Introduction: The management and outcome of a patient with a type III thoracoabdominal aortic aneurysm (TAAA) are reported. Methods: The patient was scheduled for a two-stage endovascular repair strategy but experienced a contained TAAA rupture a week before the planned second stage fenestrated endovascular repair that had been postponed from 6 weeks to 5 months. Results: Fortunately, the fenestrated device had already been delivered to the hospital; the contained rupture was thus managed endovascularly in this high-risk patient. Conclusion: Staging extensive TAAA repairs to reduce the incidence of spinal cord ischemia is associated with a risk of interval aneurysm rupture. Highlights: A staged repair is advocated whenever possible to reduce the risk of paraplegia during extensive TAAA repair. Completion of the second stage (fenestrated endografting) should be performed 6–8 weeks after the initial TEVAR procedure. If the second stage is delayed, there is a significant risk of interval aneurysm rupture.